Penyuluhan Pendidikan Anti Korupsi bagi Siswa SMK Swadaya Semarang - Suhaji; Ika Listyawati; Erawati Kartika (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2024)
The community service program packaged in this counseling activity aims to provide an understanding of anti-corruption education, especially how students are prepared to have anti-corruption values ​​consisting of 9 integrity values. This activity lasted for one day which was carried out on February 23, 2023, which was held at SMK Swadaya Semarang. Before and after the counseling, a Pre-Test and Post-Test were held for all participants. The results of the pre-test and post-test showed an increase in understanding of anti-corruption values ​​before and after the counseling. It can be interpreted that the activity went well and participants were able to understand and commit to practicing anti-corruption values ​​in life both at school and in everyday life.